The innovative design of the PANDA Barrel DIRC - Schepers, G.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Nuovo Cimento Della Societa Italiana Di Fisica C, 2019)
The Barrel DIRC of the PANDA experiment at FAIR will cleanly separate pions from kaons for the physics program of PANDA. Innovative solutions for key components of the detector sitting in the strong magnetic field of the compact PANDA target spectrometer as well as two reconstruction methods were developed in an extensive prototype program. The technical design and present results from the test beam campaigns at the CERN PS in 2017 and 2018 are discussed.
CRIS-Team Scopus Importer:2019-07-19